THEORETICAL AND EXPERIMENTAL STUDY OF GYROSCOPIC EFFECT ON OVERHUNG ROTOR - Tompodung (NIM 231 03 011), Alexander
Abstract : The gyroscopic effect or Coriolis on overhung rotor is an important aspect to be computed in critical speed. This research aimed to know effect of gyroscopic on the overhung rotor base on natural frequency fn, critical speed nc and rotor respon, had been carried out in two parts; first, it is carried out with theoretical calculation with finite element method and the second by experimental. In this research had been used 8.0 mm diameter shaft, with 121.0 mm diameter and 16.0 mm thick of disc; and had been performed in three overhung models; 31.0 mm, 53.0 mm, and 87.0 mm. From results of this research, it can be seen that natural frequency (static) resulted by calculation is not different significantly with that measured from frequency respon function FRF. The difference of theoretical and measurement result for overhung 31.0 mm is 8.5 Hz or 9.4 % and overhung 53.0 mm is 1.75 Hz or 3.18 % respectively. Measurement for critical speed have been done by making spectral map with speed interval that included critical speed. The results of measurement show that the critical variation speed is not in accordance with variation of the length of overhung because the deflection is too large when the speed approaching critical speed so the results is not acceptable.